Step
*
1
2
of Lemma
q-constraint-negative
1. x : ℕ ⟶ ℚ
2. r : ℤ
3. k : ℕ+
4. y : ℚ List
5. k ≤ ||y||
6. x k < 0
7. ¬((x k) = 0 ∈ ℚ)
8. 0 < -(x k)
9. r = 0 ∈ ℤ
10. 0 = (-(y[k - 1]) + ((-1/x k) * q-linear(k - 1;j.x j;y))) ∈ ℚ
⊢ 0 = (q-linear(k - 1;j.x j;y) + ((x k) * y[k - 1])) ∈ ℚ
BY
{ (QMul ⌜-(x k)⌝ (-1)⋅ THEN Auto THEN Try ((ParallelOp -4 THEN RelRST ⋅ THEN Auto))) }
Latex:
Latex:
1. x : \mBbbN{} {}\mrightarrow{} \mBbbQ{}
2. r : \mBbbZ{}
3. k : \mBbbN{}\msupplus{}
4. y : \mBbbQ{} List
5. k \mleq{} ||y||
6. x k < 0
7. \mneg{}((x k) = 0)
8. 0 < -(x k)
9. r = 0
10. 0 = (-(y[k - 1]) + ((-1/x k) * q-linear(k - 1;j.x j;y)))
\mvdash{} 0 = (q-linear(k - 1;j.x j;y) + ((x k) * y[k - 1]))
By
Latex:
(QMul \mkleeneopen{}-(x k)\mkleeneclose{} (-1)\mcdot{} THEN Auto THEN Try ((ParallelOp -4 THEN RelRST \mcdot{} THEN Auto)))
Home
Index